Customer Loyalty in Islamic Digital Banking: The Moderating Role of Religiosity in the Effects of E-Service Quality and Brand Image - Putri, Amanda Riany; Zaerofi, Afif; Indra, Indra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates the determinants of customer loyalty in Islamic banking in Indonesia within a digital service context. Grounded in Expectation Confirmation Theory (ECT), the study examines the effects of e-service quality and brand image on customer loyalty, with religiosity considered as both a direct and moderating variable. Using a quantitative approach, data were collected from 161 Islamic mobile banking users in the Jabodetabek region and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that e-service quality, particularly efficiency and compensation, along with brand image and religiosity, has a significant positive effect on customer loyalty, whereas responsiveness shows no significant impact. Moreover, religiosity does not moderate the relationships between e-service quality or brand image and customer loyalty. These findings suggest that customer loyalty in Islamic digital banking is driven primarily by functional service performance and brand perception, with religiosity playing a supportive but non-interactive role.